What explains the short-term dynamics of the prices of CO2 emissions? - Hammoudeh, Shawkat (2014)
Using the vector auto-regression (VAR) and the vector error-correction Models (VECM), this paper analyzes the short-term dynamics of the prices of CO2 emissions in response to changes in the prices of oil, coal, natural gas, electricity and carbon emission allowances. The results show that: (i) a positive shock to the crude oil prices has a negative effect on the CO2 allowance prices; (ii) an unexpected increase in the natural gas prices raises the price of CO2 emissions; (iii) a positive shock to the prices of the fuel of choice, coal, has virtually no significant impact on the CO2 prices; (iv) there is a clear positive effect of the coal prices on the CO2 allowance prices when the electricity prices are excluded from the VAR system; and (v) a positive shock to the electricity prices reduces the price of the CO2 allowances. We also find that the energy price shocks have a persistent impact on the CO2 allowance prices, with the largest effect occurring six months after a shock strikes. The effect is particularly strong in the case of the natural gas price shocks. Additionally, we estimate that it takes between 7.3 and 9.6 months to halve the gap between the actual and the equilibrium prices of the CO2 allowances, i.e., to erase any price over- or undervaluations after a shock strikes. Finally, the empirical findings suggest an important degree of substitution between the three primary sources of energy (i.e., crude oil, natural gas and coal), particularly, when electricity prices are excluded from the VAR system.